2017
DOI: 10.1039/c7nr02615c
|View full text |Cite
|
Sign up to set email alerts
|

Curving silver nanowires using liquid droplets for highly stretchable and durable percolation networks

Abstract: Silver (Ag) nanowires (NWs) are promising building blocks for the fabrication of stretchable electrodes, but they may undergo mechanical fracture at low tensile strains, which leads to degradation in electrical performance of Ag NW-based stretchable electrodes. Here we report on a simple route to create the percolation networks of Ag NW rings via a conventional spray coating process. We discovered that Ag NWs can be bent into curved shapes within micrometer-sized liquid droplets generated during the spraying p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 52 publications
1
18
0
1
Order By: Relevance
“…Some methods are difficult to attribute to EISA, but they also allow for the formation of certain patterns. Silver nanowires were used in [134] to form stretchable electrodes with excellent electromechanical stability subjected to periodical mechanical deformation. An array of micron-sized droplets was applied by spray coating to the surface.…”
Section: Hybrid Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some methods are difficult to attribute to EISA, but they also allow for the formation of certain patterns. Silver nanowires were used in [134] to form stretchable electrodes with excellent electromechanical stability subjected to periodical mechanical deformation. An array of micron-sized droplets was applied by spray coating to the surface.…”
Section: Hybrid Methodsmentioning
confidence: 99%
“…After the droplets impacted on the substrate, rings were formed from overlapping elastic nanowires. Such structures can well tolerate bending and stretching while retaining their electrical conductive properties [134].…”
Section: Hybrid Methodsmentioning
confidence: 99%
“…For example, Ag and copper (Cu) NWs have been acknowledged as ideal candidates for stretchable interconnects. [62][63][64] The NW provides strength and size dependent elastic property compared to bulk Ag or Cu. Importantly, the deformable NW percolation network also contributes to minimal conductivity change under strain.…”
Section: Materials Approachesmentioning
confidence: 99%
“…NWs have been particularly demonstrated and well utilized in many flexible electronics applications, owing to its efficiency for carrier flows. For example, Ag and copper (Cu) NWs have been acknowledged as ideal candidates for stretchable interconnects . The NW provides strength and size dependent elastic property compared to bulk Ag or Cu.…”
Section: Wearable Sensor Compositionmentioning
confidence: 99%
“…Interestingly, Lim and co-workers demonstrated a simple method to prepare network lms with Ag NW rings through a traditional spray-coating method (Lim et al 2017). They found that Ag NWs were elastically bent into curved shapes within micrometer-sized liquid droplets generated via the elastocapillary interaction during the spraying process (Fig.…”
Section: Ag Nw Tcesmentioning
confidence: 99%